Design And Construction Of A Web-Based Information System For Ordering Printing Services On Cv Multigraph - Hermawan, Yanto; Nugroho, Mochammad Rizky Son Adi (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Designing a Web-Based Printing Service Ordering Information System for CV Multigraph is a project aimed at developing an efficient and practical information system for online printing service orders. CV Multigraph is a printing company that offers a variety of printing services to its customers. In this research, the author designed and implemented an information system that enables customers to easily place orders through the web platform. Utilizing modern web technology, the system harnesses the power of the internet to expedite and streamline the ordering process. The system allows customers to choose their desired printing services, upload design files, select print quantities and sizes, and provide specific instructions. Upon completion of the order, customers receive real-time order status updates and confirmations. Additionally, the system facilitates CV Multigraph in managing incoming orders. Printing staff can view the list of ongoing orders, schedule production, and send confirmation messages to customers, enhancing service effectiveness and responsiveness to customer needs. The methodology used is Extreme Programming, which encompasses analysis, planning, design, coding, and testing. The system development utilizes web technologies such as HTML, CSS, JavaScript, and PHP. The result is an efficient, practical, and user-friendly printing service ordering information system for CV Multigraph customers. The system is expected to enhance customer experience, expedite the ordering process, and improve operational efficiency and customer satisfaction for CV Multigraph. Keywords: information system, ordering, printing service, CV Multigraph, web- based.